2002
DOI: 10.3904/kjim.2002.17.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Metal Stent as a Nidus for Bile Duct Stone

Abstract: Several cases of recurrent stone formation caused by a surgical material as a nidus have been reported. Recently, we experienced one case in which a migrated metal stent might have been served as a nidus for common duct stone formation. The diagnosis was confirmed by ERCP, the stone was successfully removed with endoscopic therapy. Six years ago, she had undergone a lithotripsy using a percutaneous cholangioscopy (PTCS) because of intrahepatic cile duct stoes. Six years later, she developed abdominal pain in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, progression of stone formation can be accelerated by the hypersecreted mucoglycoprotein from hyperplastic epithelia and recurrent bouts of cholangitis around the stent struts [24, 25]. Indeed, there are reports that a metal stent serves as a nidus for the formation of recurrent stones [26, 27]. In view of these observations, most research studies have suggested that the stent should be removed after a certain period (usually 6 months).…”
Section: Cpc As a Poor Prognostic Factor In Patients With Hepatolithi...mentioning
confidence: 99%
“…Furthermore, progression of stone formation can be accelerated by the hypersecreted mucoglycoprotein from hyperplastic epithelia and recurrent bouts of cholangitis around the stent struts [24, 25]. Indeed, there are reports that a metal stent serves as a nidus for the formation of recurrent stones [26, 27]. In view of these observations, most research studies have suggested that the stent should be removed after a certain period (usually 6 months).…”
Section: Cpc As a Poor Prognostic Factor In Patients With Hepatolithi...mentioning
confidence: 99%